If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4y + 2z = 6 Solving 2x + 4y + 2z = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 2x + 4y + -4y + 2z = 6 + -4y Combine like terms: 4y + -4y = 0 2x + 0 + 2z = 6 + -4y 2x + 2z = 6 + -4y Add '-2z' to each side of the equation. 2x + 2z + -2z = 6 + -4y + -2z Combine like terms: 2z + -2z = 0 2x + 0 = 6 + -4y + -2z 2x = 6 + -4y + -2z Divide each side by '2'. x = 3 + -2y + -1z Simplifying x = 3 + -2y + -1z
| 83x-2+23x-2=120 | | 5(x-3)=35 | | 2(3x+17)= | | 14x-11=-8x+7 | | (5K-3)+(K+2)+(3K-11)=K | | 4y^4-256yz^3=0 | | (5K-3)+(K+2)+(3K-11)=3K | | -6n^2+6=390 | | 14x-11=-8+7 | | (5K-3)+(K+2)+(3K-11)=6 | | -14=2v-6 | | (5K-3)+(K+2)+(3K-11)=3 | | -(x-5)=1-3x | | 3y-4x=-23 | | 23-3t=11 | | 165=-3(8m+3)-5m | | 6y+l=4y+7 | | 3p^2-6p+3=0 | | 3y-4x=-14 | | 0.03x=9.6 | | 1/3*x=20 | | -14d^2-d-49d^3=0 | | (5K-3)+(K+2)+(3K-11)=9 | | 3z^2-5z+1=0 | | 0x+0y=22 | | 4(c-1)=5(c+2) | | (5K-3)+(K+2)+(3K-11)=15 | | 4x/112 | | [(5K-3)+1]+[(K+2)+2]+[(3K-11)+3]=15 | | 200x+30x-30=y | | 9/12-5/12= | | 200x+30x-30=2040 |